Safety Profile of Porcine Factor VIII and Its Use as Hospital and Home-Therapy for Patients with Haemophilia-A and Inhibitors: the Results of An International Survey - Hay, C R M; Lozier, J N; Lee, C A; Laffan, M; Tradati, F; Santagostino, E; Ciavarella, N; Schiavoni, M; Fukui, H; Yoshioka, A; Teitel, J; Mannucci, P M; Kasper, C K (Thrombosis and Haemostasis, 1996)
A multicentre retrospective survey was conducted to re-assess the use of porcine factor VIII (HYATE:C), its side effects and the selection of patients for regular or home-therapy. 15,152,000 units of HYATE:C were used by 154 patients. The median inhibitor cross-reactivity to porcine VIIIC of 137 patients was 15%, 27% of patients lacking cross-reactivity. An absent, intermediate or brisk specific antiporcine anamnestic response was observed in 29, 40 and 31% of patients respectively. Seven patients were treated on-demand as home-therapy for a median 6.2, range 1.5-13 years. 23 further patients were treated regularly in hospital for a median of 3, range 2-7 years. This group used 8,319,000 U of porcine VIIIC for 2,000 bleeding episodes.The incidence of transfusion reactions was 0.001%, 0.64% and 2.3%, for domiciliary infusions, infusions in multiply treated inpatients, and unselected in-patient infusions, respectively. The risk of reactions was dose-related. A post-infusion fall in platelet count was common, but usually transient and clinically insignificant. This was also dose-related (r = -0.64, p = 0.002). Marked reductions in platelet count were occasionally seen, usually with intensive replacement therapy. The relative lack of side effects observed amongst patients treated at home is attributable to the low, median 33 U/kg, dose used by this group.A subgroup of inhibitor patients, identifiable by their absent or modest anamnestic response to porcine factor VIII may be treated regularly and safely with this product in small doses, over a period of years.